Irvingia gabonensis (O’Rorke) Bail polymer matrix system for controlled drug delivery (2022)
Background. Irvingia gabonensis kernel polymer has gained attention indrug delivery systems because ofits compatibility and degradation under natural and physiological conditions. Objectives. This study aimed toevaluate Irvingia gabonensis polymer asamatrix system for thecontrolled delivery of ibuprofen incomparison toxanthan gum and hydroxypropylmethylcellulose (HPMC). Materials and methods. Irvingia gabonensis polymer was extracted using established methods and dried using theoven- and freeze-drying methods. Ibuprofen tablets were prepared bydirect compression and theeffects ofpolymer concentration (10–50%), excipients (lactose, microcrystalline cellulose and dicalcium phosphate dihydrate) and polymers (xanthan gum and HPMC) onthemechanical and drug release proper¬ties ofthetablets were evaluated. Density measurements and theHeckel and Kawakita equations were used todetermine thecompression properties ofthetablets. Friability, crushing strength and thecrushing strength–friability ratio (CSFR) were used toevaluate themechanical properties ofthetablets, while dis¬solution times were used toevaluate drug release from thematrices. Thedrug release mechanisms were determined byfitting thedissolution data into classic kinetic equations. Results. Irvingia gabonensis polymer deformed plastically with afast onset and ahigh amount ofplastic deformation compared with xanthan gum and HPMC. This polymer was directly compressible and formed intact non-disintegrating tablets; themechanical and dissolution properties ofIrvingia gabonensis polymer tablets generally decreased with increasing concentration ofibuprofen. Theranking ofdissolution times was xanthan gum> freeze-dried Irvingia gabonensis> HPMC> oven-dried Irvingia gabonensis. Theaddition oftheexcipients improved themechanical properties ofthetablets, aided ibuprofen release, and altered therelease kinetics, which was largely defined bytheKorsmeyer–Peppas model. Increasing theproportion ofxanthan gum and HPMC inthematrices resulted inadecreased amount ofibuprofen released after 9h, with xanthan gum having agreater effect. Conclusions. Irvingia gabonensis polymer matrices may be effective inthepreparation ofcontrolled release tablets, and their right combination with xanthan gum orHPMC could provide atime-independent release for longer durations.